A 23‐year‐old patient with bilateral hypoplastic thumbs and toes: A case report - Suaad Hamsho; Mouhammed Sleiay; Mohammed Alaswad; Hasan Alsmodi; Khaled Al‐Hakeem (Clinical Case Reports, 2024)
Key Clinical Message However, it is noteworthy that certain patients with minor functional limitations in their hand may have experienced undiagnosed thumb hypoplasia during their childhood years. These individuals may have successfully adapted to their condition without seeking medical intervention and may express a preference for nonintervention (as in this case). Abstract Thumb hypoplasia is a congenital underdevelopment of the thumb, accounting for 5%–15% of congenital hand disorders. It occurs equally among both genders and can affect both thumbs. The condition is categorized using Blauth's classification with Type I being the mildest form. We report a 23‐year‐old Syrian male presented with a bilateral restriction in opposition movement when using a pen or razor. Clinical examination and x‐ray imaging revealed a bilateral Type I hypoplastic thumb with bilateral minimal hypoplasia of the toes. Despite the surgical treatment options available, the patient opted not to undergo surgery due to his adaptation to his condition. Hypoplastic thumb Type I is a congenital condition characterized by underdevelopment of the thumb. Bilateral thumb hypoplasia with toes hypoplasia is extremely rare. A full systemic evaluation should be done due to its associations with other syndromic manifestations and treatment options are discussed concerning the best functional outcomes and patient preferences.